Big Data and Java are integrated with machine learning - Anis Ahmed Qazi; Ehsan Abbas (International Journal of Multidisciplinary Sciences and Arts, 2024)
This in-depth investigation explores the revolutionary nexus of Java, Big Data, and Machine Learning (ML), clarifying the innovations and synergies that result from their integration. The voyage commences with a summary of the past, following the growth from Java's fundamental function in high-level development to the revolutionary influence of Big Data frameworks such as Apache Hadoop and Apache Spark. The story then delves into the fundamentals of machine learning in Java, highlighting its adaptability, rich library support, and crucial role in building strong ML pipelines. The investigation delves into the transformative power of Big Data frameworks, highlighting the distributed file system of Hadoop and the in-memory processing capabilities of Spark. We observe the significant effects of this convergence on a variety of industries through real-world case studies, from e-commerce personalized suggestions to fraud detection in banking. The insights gained from these implementations highlight how crucial it is to use ML models with ethical considerations, interdisciplinary cooperation, and ongoing learning. The following sections cover the nuances of data preprocessing, including the use of Java in ETL workflows, scalable feature engineering using Big Data frameworks, and data quality assurance via transformation and cleansing. ML model deployment is the major focus, along with an exploration of the Java runtime environment, micro services architecture, and crucial aspects of model robustness monitoring and maintenance. The investigation concludes with a focus on case studies and success stories that demonstrate the real-world effects of this convergence in sectors like e-commerce, finance, and healthcare. These real-world examples highlight the accomplishments of companies like Netflix, Uber, Airbnb, and others and provide insightful information about how well integration works to accomplish a range of business objectives.